2009
DOI: 10.1128/mcb.00275-09
|View full text |Cite
|
Sign up to set email alerts
|

A Randomly Integrated Transgenic H19 Imprinting Control Region Acquires Methylation Imprinting Independently of Its Establishment in Germ Cells

Abstract: The imprinted expression of the mouse Igf2/H19 locus is governed by the differential methylation of the imprinting control region (ICR), which is established initially in germ cells and subsequently maintained in somatic cells, depending on its parental origin. By grafting a 2.9-kbp H19 ICR fragment into a human ␤-globin yeast artificial chromosome in transgenic mice, we previously showed that the ICR could recapitulate imprinted methylation and expression at a heterologous locus, suggesting that the H19 ICR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
33
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 39 publications
(68 reference statements)
9
33
1
Order By: Relevance
“…Because the endogenous H19 ICR is fully methylated in sperm, the postfertilization methylation activity at the endogenous locus, if present, is normally difficult to reveal. Our previous results (Matsuzaki et al, 2009) and those of others (Gebert et al, 2010;Park et al, 2004;Puget et al, 2015) suggested that the gametic methylation of the H19 ICR was governed by signals from surrounding sequences, i.e. those located outside the 2.9-kb H19 ICR region.…”
Section: Methylation Acquisition At the Transgenic H19 Icr In Early Ementioning
confidence: 99%
See 2 more Smart Citations
“…Because the endogenous H19 ICR is fully methylated in sperm, the postfertilization methylation activity at the endogenous locus, if present, is normally difficult to reveal. Our previous results (Matsuzaki et al, 2009) and those of others (Gebert et al, 2010;Park et al, 2004;Puget et al, 2015) suggested that the gametic methylation of the H19 ICR was governed by signals from surrounding sequences, i.e. those located outside the 2.9-kb H19 ICR region.…”
Section: Methylation Acquisition At the Transgenic H19 Icr In Early Ementioning
confidence: 99%
“…Preimplantation embryos were embedded in agarose beads and treated with sodium bisulfite as described previously (Matsuzaki et al, 2009). Genomic DNA extracted from postimplantation embryos (E8.5), adult male sperm, or the tail tips of ∼1-week-old animals was treated with sodium bisulfite using the EZ DNA Methylation Kit (Zymo Research).…”
Section: Dna Methylation Analysis By Bisulfite Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgene-specific nested PCR, cloning, and sequencing analysis were performed as described previously (23,24). Subregions of the H19 ICR (region I, nucleotides 1245 to 1995; region II, nucleotides 2845 to 3432; region II=, nucleotides 3050 to 3432; GenBank accession no.…”
Section: Methodsmentioning
confidence: 99%
“…The cumulus cells were removed by treatment with hyaluronidase and then washed repeatedly with M2 medium and PBS. Four to 14 blastocysts or 21 to 38 oocytes were embedded in agarose beads and treated with sodium bisulfite as described previously (24).…”
Section: Methodsmentioning
confidence: 99%